2018
DOI: 10.15537/smj.2018.1.21169
|View full text |Cite
|
Sign up to set email alerts
|

Single-center experience in the surgical treatment of combined lung Echinococcosis

Abstract: Objectives:To compare results of surgical treatment and complications of patients with unilateral or bilateral thoracic and combined pulmonary echinococcosis.Methods:This cross-sectional analysis of a prospective study was conducted in the Department of Thoracic and Pediatric Surgery, Scientific Center of Surgery, Almaty, Kazakhstan among 598 patients with pulmonary echinococcosis, who had surgical treatment with various surgical methods, depending on the prevalence of echinococcosis, as follows: right lung in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It was shown that PI had success as a sclerosing agent in spaces with surrounded inline epithelium in recurrent fluid accumulation cases (26). It is reported that PI is a safe and effective sclerosing agent in lymphocele, pleural effusion, empyema, pericardial effusion, thyroid cysts, hydrocele, and lung Echinococcosis (26)(27)(28). PI was first used as a sclerotherapy agent by Teruel et al (29).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that PI had success as a sclerosing agent in spaces with surrounded inline epithelium in recurrent fluid accumulation cases (26). It is reported that PI is a safe and effective sclerosing agent in lymphocele, pleural effusion, empyema, pericardial effusion, thyroid cysts, hydrocele, and lung Echinococcosis (26)(27)(28). PI was first used as a sclerotherapy agent by Teruel et al (29).…”
Section: Discussionmentioning
confidence: 99%
“…The role of surgery is paramount in the treatment of this disease, for it is the only way to achieve a radical cure (9). Since the complete evacuation of the cyst and removal of the endocyst are essential in the radical resection, thoracotomy is recognized as the standard surgical method due to its ability to provide a better operating space for avoiding contamination and spillage (10). With the development of minimally invasive surgery, video-assisted thoracoscopic surgery (VATS) has been more widely applied in treating benign and malignant pulmonary diseases (11,12).…”
Section: Introductionmentioning
confidence: 99%